A comprehensive study on physical fitness of Wushu routine athletes based on video-driven core strength training mechanism in wireless network - Li, Long; Geok, Soh Kim; Li, Hu; Talib, Othman; Sun, He; Lam, Soh Kim (Springer, 2022)
Under the condition of high performance sports, the physical state of Wushu routine athletes is very different from that of commons, and they need the strength support of the core muscle tissue. Specifically, core strength training has an important impact on the physical stability of Wushu routine athletes, and strengthening core strength training can improve their physical quality. In core strength training, video training method can make up for the shortcomings of traditional training methods. In addition, with the rapid development of wireless network technology, video service has become the mainstream application of mobile Internet. At the same time, users' experience needs for video services under wireless networks have gradually changed, and the traditional video Quality of Experience (QoE) is difficult to fully reflect users' actual experience quality. Therefore, this paper proposes a QoE prediction model based on core strength training video information, data of quality of service, and behaviors of Wushu routine athletes. The experimental results show that the QoE prediction model of core strength training video converges rapidly in the training process, and has a good fitting effect on the training set and verification set. Furthermore, the QoE prediction model proposed in this paper can improve the accuracy of subjective QoE of Wushu routine athletes in wireless network environment. The construction of QoE prediction model is the premise of optimizing QoE. An effective QoE prediction model can reflect the real video experience of Wushu routine athletes and provide a comprehensive and accurate QoE reference for the construction of core strength training video, so as to improve the physical quality of Wushu routine athletes.